Dynamic sustainable business modelling: exploring the dynamics of business model components considering the product development framework - Maresova, Petra; Javanmardi, Ehsan; Maskuriy, Raihan; Selamat, Ali; Kuca, Kamil (Routledge, 2022)
Business systems are a subclass of dynamic, complex systems; the plurality of multifarious and interwoven factors affecting a business system makes prediction, modeling, and decision-making challenging for the players in such systems. This study conceptualises dynamic business modeling from a sustainability viewpoint by investigating the basic principles, requirements, and methodological limitations, as well as gaps in the business model design literature. This conceptual model combines an adapted business model canvas and system dynamics modeling using an up-to-date review. The studies used in this systematic review were retrieved from the Scopus and Web of Science databases between 2010 and 2021. The total number of publications in all databases was 422. However, following an in-depth investigation of these publications, 164 papers were selected for further review. Based on the business model canvas, the interactions between different business dimensions and the impact on environmental stakeholders were examined. Finally, a dynamic, sustainable business model canvas is conceptualised and developed. The findings suggest that the proposed system dynamics business modeling approach can frame the environmental, social, and economic drivers of value creation in a causal feedback structure and overcome the gaps and criticisms of existing business model design tools.